Reproductive biology and diet of the grey sharpnose shark Rhizoprionodon oligolinx Springer, 1964 (Chondrichthyes: Carcharhinidae) from the north-eastern Arabian Sea - Purushottama, G. B.; ., Thakurdas; Ramasubramanian, V.; Dash, Gyanaranjan; Akhilesh, K. V.; Ramkumar, S.; Kizhakudan, Shoba Joe; Singh, V. V.; Zacharia, P. U. (Indian Journal of Fisheries, 2018)
Information on reproductive biology is presented for the grey sharpnose shark Rhizoprionodon oligolinx Springer, 1964 (Chondrichthyes: Carcharhiniformes), collected off the north-west coast of India in the Arabian Sea. A total of 711 individuals, of 27.0 to 93.0 cm total length (TL), 180 to 2600 g total weight (TW) were used for the study. The lengthweight relationships were significantly different between the sexes. The size-at-maturity (Lm50) for females and males was estimated to be 62.3 and 59.5 cm TL respectively. Number of embryos ranged from 1 to 7 and the size at birth was estimated between 25 to 30 cm TL. Overall sex ratio favoured the females slightly at the rate of 1.27:1. There was significant positive correlation between maternal TL and number of embryos (p